2021
DOI: 10.3390/ijms22095044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Differentiated Macrophage-Like Cells on the Transcriptional Toxicity Profile of CuO Nanoparticles in Co-Cultured Lung Epithelial Cells

Abstract: To mimic more realistic lung tissue conditions, co-cultures of epithelial and immune cells are one comparatively easy-to-use option. To reveal the impact of immune cells on the mode of action (MoA) of CuO nanoparticles (NP) on epithelial cells, A549 cells as a model for epithelial cells have been cultured with or without differentiated THP-1 cells, as a model for macrophages. After 24 h of submerged incubation, cytotoxicity and transcriptional toxicity profiles were obtained and compared between the cell cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 65 publications
(100 reference statements)
0
20
0
Order By: Relevance
“…Surprisingly, no ROS increase in response to CD-PEI600 was measured in A549 and THP-1 cells when combined in the co-culture model. Although ROS production is a commonly used biomarker in nanotoxicology studies carried out on mono-culture models, it is still poorly monitored in co-culture models [ 20 , 43 , 63 , 64 , 65 , 66 ]. From the few reports found in the literature, it appears that NPs have no [ 66 ] or little impact on oxidative stress in co-culture models associating epithelial cells and macrophages [ 43 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Surprisingly, no ROS increase in response to CD-PEI600 was measured in A549 and THP-1 cells when combined in the co-culture model. Although ROS production is a commonly used biomarker in nanotoxicology studies carried out on mono-culture models, it is still poorly monitored in co-culture models [ 20 , 43 , 63 , 64 , 65 , 66 ]. From the few reports found in the literature, it appears that NPs have no [ 66 ] or little impact on oxidative stress in co-culture models associating epithelial cells and macrophages [ 43 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by the fact that the cellular interplay of the different cell types may help the cells dealing with oxidative stressors [ 20 ]. On the contrary, it has been recently reported that genes associated with antioxidant defense mechanisms ( NFKB1 , KEAP1 , and NFE2L2 ) exerted slightly lower effects in the co-culture associating A549 and THP-1 cells as compared to the A549 mono-culture [ 65 ]. Assessing how antioxidant systems are modulated in response to CDs in mono- and co-culture models could be an interesting point to investigate in future work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations